SENJANGAN ANGGARAN : STUDI ATAS PENGENDALIAN ANGGARAN, IKLIM KERJA ETIS DAN PERSEPSI KEADILAN PROSEDURAL - Galih Fajar Muttaqin (FEB Universitas Sultan Ageng Tirtayasa, 2016)
Abstract Data was collected by distributing questionnaires using purposive sampling technique to the respondents. Respondents are middle and lower level managers in Banten which of course involved in the budgeting process, with a total of 41 respondents at public organization. Data were analyzed using SEM with the help of SmartPLS version 2.0. Results from this study revealed that the variable Budgetary Control Effectiveness and Ethical Work Climate has a positive and significant impact on the Procedural Justice perception. Variable Ethical Work Climate and Procedural Justice Perception Climate has a negative and significant impact on the Propensity to Create Budgetary Slack, while the variable Budgetary Control Effectiveness no significant effect on the Propensity to Create Budgetary Slack.